2022
DOI: 10.3389/fenvs.2022.822811
|View full text |Cite
|
Sign up to set email alerts
|

Factor Mobility, Industrial Transfer and Industrial Carbon Emission: A Spatial Matching Perspective

Abstract: This paper proposes a dynamic industrial transfer index for the first time to characterize the spatial matchability of factor mobility and industrial transfer, and then explores the correlation between factor mobility, industrial transfer and industrial carbon emission intensity by using panel data from 30 provinces in China during 2004–2019. The results show that China’s ability to reduce carbon emissions is improving, and the intensity of industrial carbon emission has dropped by 44.84%. In addition, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Consequently, it creates a favorable market environment for optimizing and upgrading industrial structures. Industrial activities are significant contributors to carbon emissions; numerous studies have demonstrated the role of industrial structure upgrading in emission reduction [29][30][31], which will not be reiterated here.…”
Section: Structure Effectmentioning
confidence: 88%
“…Consequently, it creates a favorable market environment for optimizing and upgrading industrial structures. Industrial activities are significant contributors to carbon emissions; numerous studies have demonstrated the role of industrial structure upgrading in emission reduction [29][30][31], which will not be reiterated here.…”
Section: Structure Effectmentioning
confidence: 88%
“…The amount of carbon emitted for every unit of gross industrial production is referred to as industrial carbon emission intensity (ICEI) [39,40]. ICEI can reflect the relationship between CE and industrial development.…”
Section: Calculation Methods Of Carbon Emissionsmentioning
confidence: 99%
“…With the increasing severity of climate problems, the issue of carbon transfer has gradually attracted the attention of scholars, who have focused on exploring the causes (Dong et al , 2022), quantitative measurements (Ji et al , 2020) and flow directions (Zheng et al , 2022) of carbon transfer. López et al (2019) found that American multinational enterprises transferred carbon emissions from domestic production to other countries through cross-border investments.…”
Section: Literature Reviewmentioning
confidence: 99%